2023
DOI: 10.1039/d3ra01357j
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic removal of 2-chlorophenol from water by using waste eggshell-derived calcium ferrite

Abstract: A new approach to recycling low-value eggshell food waste was to produce a CaFe2O4 semiconductor with a narrow band gap (Eg = 2.81 eV) via hydrothermal treatments of powdered eggshell suspended in aqueous ferric salt (Fe3+) solutions at varying Fe loadings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 70 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…On running the scavenger test it was found that, with addition of radical scavengers the removal efficiency of 2-chlorophenol was lowered reflecting the scavenger reactions (Scheme 23). 84 It is important to note that amongst various other biowaste being generated around the globe, eggshell has attracted considerable attention of scientists in all fields, along with proving its expertise too. The global availability and non-perilous nature are a boon of all times as far as green chemistry and sustainable chemical reactions are concerned (Scheme 23).…”
Section: Egg Shell Powder As a Catalyst For Organic Transformationsmentioning
confidence: 99%
“…On running the scavenger test it was found that, with addition of radical scavengers the removal efficiency of 2-chlorophenol was lowered reflecting the scavenger reactions (Scheme 23). 84 It is important to note that amongst various other biowaste being generated around the globe, eggshell has attracted considerable attention of scientists in all fields, along with proving its expertise too. The global availability and non-perilous nature are a boon of all times as far as green chemistry and sustainable chemical reactions are concerned (Scheme 23).…”
Section: Egg Shell Powder As a Catalyst For Organic Transformationsmentioning
confidence: 99%